KunstWerk : Bildende Kunst bei Bayer. - Bott, Elisabeth; Miksche, Uta; Ohle, Reiner Ernst (Leverkusen : Bayer AG, 1992)
Büttner, Werner ; Knoebel, Imi ; Dibbets, Jan ; Hernandez Pijnan, Joan ; Canright, Sarah ; Iglesias, Cristina ; Duff, Diana ; Fischer, Mona ; Oehlen, Albert ; Oehlen, Markus ; Schmit, Tomas ; Herold, Georg ; Abramovic, Marina & Ulay ; Antonsen, Stephan ; Morill, Michael ; etc.
Duits
boek